Aktualisasi Nilai-Nilai Hadis tentang Musyawarah dalam Manajemen Supervisi Akademik - Febiana, Ays Risma; Fitriah, Salsa Billa; Sahudi, Sahudi (Jurnal Kependidikan Islam, 2024)
Academic supervision is frequently perceived as an administrative and evaluative activity that positions teachers as mere assessment objects. This study aims to analyze the actualization of Prophetic ethics regarding consultation within the academic supervision cycle at SMP Negeri 3 Krian. A qualitative approach with a case study design was employed using observations, interviews, and documentation of the 2022/2023 supervision program. Data were analyzed thematically through condensation, categorization, matrix display, and conclusion drawing. The findings indicate that consultation was actualized in target coordination, individual group approaches, joint findings discussion, and collective follow up formulation. This model successfully transforms administrative control into egalitarian professional learning. However, its effectiveness remains constrained by unequal supervisor distribution and potential assessment subjectivity. This study recommends a reflective consultation supervision cycle integrating participation, trustworthiness, justice, benefit, and accountability to strengthen teacher agency and school collaborative culture.